2014
DOI: 10.1371/journal.pone.0098878
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Beta-(1,3)-D-Glucan in House Dust at Age 7–10 Is Associated with Airway Hyperresponsiveness and Atopic Asthma by Age 11–14

Abstract: BackgroundMould exposure has been linked to childhood asthma and bronchial hyper-responsiveness. Few studies have assessed beta-(1,3)-d-glucan (beta-glucan), a significant fungal cell wall constituent, in relation to asthma in adolescence.ObjectiveTo determine whether house dust-derived beta-glucan exposure at age 7–10 is associated with the development and persistence of atopic and non-atopic asthma, and bronchial hyper-responsiveness (BHR) by age 11–14.MethodsDust samples were collected from the 1995 Study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Qualitative assessments of fungal exposure in the form of mildew odor or visible mold have been linked with increased risk of allergic rhinitis and asthma 96-98 . This finding is corroborated by studies using quantitative fungal measures, such as DNA-based analyses 99 and β-1,3-glucan measurements 100, 101 . In a longitudinal birth cohort of high-risk infants, Iossifova et al demonstrated an increased risk of asthma with exposure to low levels of β-1,3-glucan but a protective effect upon exposure to levels of β-1,3-glucan greater than 60 micrograms per gram of dust 97, 100 , suggesting a possible nonlinear dose-response relationship similar to that observed for HDM allergen.…”
Section: Indoor Allergen Exposuresupporting
confidence: 56%
“…Qualitative assessments of fungal exposure in the form of mildew odor or visible mold have been linked with increased risk of allergic rhinitis and asthma 96-98 . This finding is corroborated by studies using quantitative fungal measures, such as DNA-based analyses 99 and β-1,3-glucan measurements 100, 101 . In a longitudinal birth cohort of high-risk infants, Iossifova et al demonstrated an increased risk of asthma with exposure to low levels of β-1,3-glucan but a protective effect upon exposure to levels of β-1,3-glucan greater than 60 micrograms per gram of dust 97, 100 , suggesting a possible nonlinear dose-response relationship similar to that observed for HDM allergen.…”
Section: Indoor Allergen Exposuresupporting
confidence: 56%
“…59 Certain types of fungi have been shown to be associated with protection from asthma and may also play a key role in influencing the composition of the microbiota and immune system. 62 High levels of fungal exposure have been strongly implicated in the development and prevalence of asthma. 62 High levels of fungal exposure have been strongly implicated in the development and prevalence of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, no difference was found in any of the concentrations between sensitized and non-sensitized cases. In contrast, Maheswaran et al [56] found that increased β−1,3-glucan concentration was significantly associated with increased prevalence of atopic asthma. No association was found between β−1,3-glucan and non-atopic asthma.…”
Section: Role Of Fungal Exposure In Asthma Healthmentioning
confidence: 93%